Social Service Movement as An Effort to Help People Around Universitas Kadiri andReduce Covid-19 Movement Space - Komari Ana; Lolyka Dewi Indrasari; Afiff Yudha Tripariyanto; Heribetus Budi Santosa; Sri Rahayuningsih (Universitas Pancasakti Tegal, 2021)
Community service as one form of implementation of tri dharma college. Social service movement to help the economy and reduce the movement space of covid-19 as a goal achieved. The intended subject is to students at Budi Mulia Orphanage and seniors in Pojok village, Mojoroto district. Preparation of activities includes schedule arrangement, location arrangement, questionnaires, and attendance of participants. On April 25, 2021, at the Orphanage